2014
DOI: 10.1210/jc.2013-4133
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease Is Associated With Increased Carotid Intima-Media Thickness Only in Type 2 Diabetic Subjects With Insulin Resistance

Abstract: NAFLD is very common in subjects with type 2 diabetes, but NAFLD not accompanied by insulin resistance is not associated with a carotid atherosclerotic burden. However, having both NAFLD and insulin resistance seemed to be an independent predictor of increased C-IMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 15 publications
2
42
1
1
Order By: Relevance
“…Among diet-controlled T2DM individuals the significant increase of cIMT in the presence of NAFLD is largely explained by HOMA-estimated IR [18]. Recently, Kim et al concluded that NAFLD not accompanied by insulin resistence is not associated with a carotid atherosclerotic burden [19]. We could not demonstrate a correlation between cIMT and HOMA-IR in our T2DM patients.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Among diet-controlled T2DM individuals the significant increase of cIMT in the presence of NAFLD is largely explained by HOMA-estimated IR [18]. Recently, Kim et al concluded that NAFLD not accompanied by insulin resistence is not associated with a carotid atherosclerotic burden [19]. We could not demonstrate a correlation between cIMT and HOMA-IR in our T2DM patients.…”
Section: Discussioncontrasting
confidence: 70%
“…Many works showed no association between the degree of liver steatosis and early atherosclerosis as measured by US [14][15][16] or computed tomography [17] in T2DM patients. In contrast, other studies in T2DM subjects indicated a significant increase of cIMT in the presence of NAFLD that could be partially explained by the presence of insulin resistance [18,19]. Body fat distribution seems to play an important role in atherosclerosis progression in non-diabetic patients with NAFLD but in T2DM subjects this aspect is not completely known.…”
Section: Introductionmentioning
confidence: 79%
“…Additionally, antioxidative markers may be inversely associated with TG levels in early preclinical atherosclerosis even with normal levels of plasma cholesterol [34], and our group has previously demonstrated that liraglutide is able to reduce markers of oxidative stress in patients with T2DM [35]. Kim SK et al [36] have interestingly reported that nonalcoholic fatty liver disease (NAFLD) is very common in subjects with T2DM, but NAFLD not accompanied by insulin resistance is not associated with a carotid atherosclerotic burden. However, in this latter study [36], coexistence of NAFLD and insulin resistance seemed to be an independent predictor of increased cIMT.…”
Section: Discussionmentioning
confidence: 99%
“…Kim SK et al [36] have interestingly reported that nonalcoholic fatty liver disease (NAFLD) is very common in subjects with T2DM, but NAFLD not accompanied by insulin resistance is not associated with a carotid atherosclerotic burden. However, in this latter study [36], coexistence of NAFLD and insulin resistance seemed to be an independent predictor of increased cIMT. Therefore, a greater cIMT reduction in subjects with NAFLD and insulin resistance in our study remains a strong possibility.…”
Section: Discussionmentioning
confidence: 99%
“…reported that NAFLD was associated with elevated CIMT, independent of conventional CVD risk factors. On the contrary, NAFLD not accompanied by insulin resistance was not associated with increased CIMT in a recent study including patients with type 2 diabetes . In a small study including 40 Asian Indians with NAFLD and 40 healthy controls, NAFLD was found to be significantly associated with increased CIMT independent of obesity and metabolic syndrome .…”
Section: Discussionmentioning
confidence: 74%